(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Introduction: Establishment of personal identity in forensic science involves chiefly determination of sex, race, age and stature .If the sex of an individual is known, it can be helpful to exclude a large number of suspects from the investigation. Cheiloscopy is an upcoming tool for determination of sex of an individual. Objective: The aim of the study was to determine whether cheiloscopy behold the potential for determination of sex. Materials and Method: The study was conducted on 100 students, 50 males and 50 females belonging to the age group of 18-23 years. Lip prints were recorded by applying lipstick and then transparent cellophane tape to the lips which was then stuck to a white bond paper. They were studied and classified by two separate examiners. The results were statistically analyzed using percentages and applying Chi – square test for goodness of fit to see the difference in types in the two sexes . Result: No two lip prints matched each other. The commonest lip print pattern was Type I in females and Type IV in males. The percentage of accuracy was 89% for examiner1 and 91% for examiner2 in correct sex identification. The results were statically significant. Conclusion: This study reveals that lip prints are unique and cheiloscopy beholds the potential for determination of sex.